2006
DOI: 10.1159/000094803
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype differentiation in <i>Chromaphyosemion</i> killifishes (Cyprinodontiformes, Nothobranchiidae). II: Cytogenetic and mitochondrial DNA analyses demonstrate karyotype differentiation and its evolutionary direction in <i>C. riggenbachi</i>

Abstract: African killifishes of the genus Chromaphyosemion show a high degree of phenotypic and karyotypic diversity. The latter is especially pronounced in C. riggenbachi, a morphologically defined species restricted to a small distribution area in Cameroon. This study presents a detailed reconstruction of karyotype differentiation within C. riggenbachi using conventional Giemsa staining and sequential chromosome banding as well as a phylogenetic analysis based on part of the mitochondrial (mt) cytochrome b gene from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 71 publications
3
26
1
Order By: Relevance
“…In fact, before fixation, rearrangements are present in a transitory heterozygous state in populations. Similarly, as in some individuals of the killifish Chromaphyosemion riggenbachi [Völker et al, 2006], polymorphism due to a paracentric inversion was also found in C. undecimalis , indicating ongoing chromosomal reorganizations in Centropomus. It is also noteworthy that snooks are protandric hermaphrodites which are born as males and later become females [Taylor et al .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In fact, before fixation, rearrangements are present in a transitory heterozygous state in populations. Similarly, as in some individuals of the killifish Chromaphyosemion riggenbachi [Völker et al, 2006], polymorphism due to a paracentric inversion was also found in C. undecimalis , indicating ongoing chromosomal reorganizations in Centropomus. It is also noteworthy that snooks are protandric hermaphrodites which are born as males and later become females [Taylor et al .…”
Section: Discussionmentioning
confidence: 55%
“…Since paracentric inversions do not affect the morphology of the chromosomes, a number of markers are required to reveal them. In some cases, these inversions were detected when NORs were involved [Moreira-Filho et al, 1984;Ráb et al, 2002;Cardoso et al, 2013] and, less frequently, by changes in the position of 5S rDNA sites [Kavalco et al, 2004] or GC-rich heterochromatic regions [Völker et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive chromosome preparation was made from regenerating fin tissue according to Völker et al (2006). Sequential CMA 3 -fluorescence banding (Sola et al 1992), Giemsa staining, and AgNO 3 -staining (Howell and Black, 1980) were performed to detect NORs (i.e., major rDNA clusters).…”
Section: Methodsmentioning
confidence: 99%
“…Unlike other Cyprinodontiformes, H. antenori showed no evidence of AT-rich regions in the karyotype, as hypothesized due to intense structural rearrangements occurring in chromosomes of some species [39]. This condition, associated with the occurrence of two GC-rich regions, coincident with nucleolar organizer regions, suggests lower participation of Robertsonian translocation events, frequent in several species [15, 19, 3840].…”
Section: Discussionmentioning
confidence: 85%
“…More recently, extreme evolutionary dynamics involving chromosomal rearrangements has also been identified in annual African fish species of the genus Chromaphyosemion , where substantial cytogenetic changes related to chromosome morphology, besides banding patterns and/or diploid number between analyzed populations, were observed [39]. The karyotypic diversification among populations and species of this genus is strongly modeled by mechanisms of Robertsonian translocation, as well as other complementary processes including heterochromatinization [40].…”
Section: Discussionmentioning
confidence: 99%